Student Involvement in Community Activities Related to Educational Programs - Danang Prasetyo; Yoga Ardian Feriandi; Sukron Mazid (Indonesian Journal Of Educational Research and Review, 2021)
The development of the object of study of citizenship education material is not fixed in classrooms carried out in formal schools, but can also be carried out in community activities known as socio-cultural citizenship. This is the purpose of this study by describing the application of civic education in the social sphere, namely the involvement of students from various universities who are members of the Atap Senja Community School. The method used is a case study on student involvement in community activities related to educational programs carried out in the community. The results of this study indicate that the concept of civic civic education can be carried out by involving community civic education that develops in the community, namely the Atap Senja Community School in Yogyakarta. This community consists of students from various universities in Yogyakarta. Activities carried out by providing learning assistance and attention to the development of morality for children who do not receive formal education at school. Funding for activities carried out by this community comes from membership fees or what has been called volunteers. The activities carried out by this community are proof of the participation of young citizens in changing the educational conditions of school dropouts, with various kinds of financial limitations. This can be interpreted as a form of civic engagement with the state, because indirectly these community activities will also affect and improve the conditions of education in Indonesia.